Institusionalisasi Program Green Entrepreneurship: Program SAMADE Kabupaten Kampar Riau - Irham Dani; Hempri Suyatna (Universitas Tribhuwana Tunggadewi, 2026)
Economic vulnerability and ecological pressures resulting from the dominance of oil palm plantations have led to dependence on a single commodity, low levels of farmer innovation and entrepreneurial capacity, and environmentally damaging conventional agricultural practices. This study aims to describe the dynamics and inter-actor relationships in the process of developing the institutionalization of the SAMADE Program in Kampar Regency, Riau Province. The study employs a qualitative method with a phenomenological approach, using in-depth interviews, participatory observation, and documentation studies involving various actors, including farmers, agricultural extension officers, local government officials, and financial institutions. A total of 18 informants participated in this study. The findings reveal that the institutionalization process of the SAMADE Program evolves dynamically through seven stages: initial contact, awareness, understanding, trial, adoption, institutionalization, and the internalization of green entrepreneurship values. Agricultural extension officers play a pivotal role at each stage, acting as key facilitators and mentors in the implementation of sustainable agricultural practices. The main supporting factors for program success include community solidarity, pro-environmental local government policies, and partnerships with financial institutions. Meanwhile, constraints arise in the form of limited capital, entrenched conventional farming cultures, and restricted access to technology.Kerentanan ekonomi dan tekanan ekologis akibat dominasi perkebunan kelapa sawit yang menimbulkan ketergantungan pada satu komoditas, rendahnya inovasi dan kapasitas kewirausahaan petani, serta praktik pertanian konvensional yang merusak lingkungan. Penelitian ini bertujuan untuk menggambarkan dinamika dan relasi antaraktor dalam proses pengembangan institusionalisasi Program SAMADE di Kabupaten Kampar, Provinsi Riau. Penelitian ini menggunakan metode kualitatif pendekatan fenomenologi dengan teknik wawancara mendalam, observasi partisipatif, dan studi dokumentasi terhadap berbagai aktor, antara lain petani, penyuluh, pemerintah daerah, serta lembaga keuangan. Jumlah informan yang dilibatkan dalam penelitian ini sebanyak 18 orang. Hasil penelitian menunjukkan bahwa proses institusionalisasi Program SAMADE berlangsung secara dinamis melalui tujuh tahap: kontak awal, kesadaran, pemahaman, uji coba, adopsi, dan pelembagaan hingga internalisasi nilai green entrepreneurship. Peran penyuluh pertanian menjadi kunci dalam setiap tahap, berfungsi sebagai fasilitator dan pendamping utama dalam penerapan praktik pertanian berkelanjutan. Faktor pendukung utama keberhasilan program meliputi solidaritas komunitas, dukungan kebijakan pemerintah daerah yang pro-lingkungan, dan kemitraan dengan lembaga keuangan. Sementara itu, hambatan muncul dalam bentuk keterbatasan modal, budaya bertani konvensional yang sulit diubah, serta keterbatasan teknologi.